Controversies in the management of patients with soft tissue sarcoma: Recommendations of the Conference on State of Science in Sarcoma 2022. (February 2023) - Rothermundt, Christian; Andreou, Dimosthenis; Blay, Jean-Yves; Brodowicz, Thomas; Desar, Ingrid M.E.; Dileo, Palma; Gelderblom, Hans; Haas, Rick; Jakob, Jens; Jones, Robin L.; Judson, Ian; Kunz, Wolfgang G.; et al.
Abstract: Background: Owing to the rarity and heterogeneity in biology and presentation, there are multiple areas in the diagnosis, treatment and follow-up of soft tissue sarcoma (STS), with no, low-level or conflicting evidence. Methods: During the first Consensus Conference on the State of Science in Sarcoma (CSSS), we used a modified Delphi process to identify areas of controversy in the field of sarcoma, to name topics with limited evidence-based data in which a scientific and knowledge gap may remain and a consensus statement will help to guide patient management. We determined scientific questions which need to be addressed in the future in order to generate evidence and to inform physicians and caregivers in daily clinical practice in order to improve the outcomes of patients with sarcoma. We conducted a vote on STS key questions and controversies prior to the CSSS meeting, which took place in May 2022. Results: Sixty-two European sarcoma experts participated in the survey. Sixteen strong consensus (≥95%) items were identified by the experts, as well as 30 items with a ≥75% consensus on diagnostic and therapeutic questions. Ultimately, many controversy topics remained without consensus. Conclusions: In this manuscript, we summarise the voting results and the discussion during the CSSS meeting. Future scientific questions, priorities for clinical trials, registries, quality assurance, and action by stakeholders are proposed. Platforms and partnerships can support innovative approaches to improve management and clinical research in STS. Highlights: First consensus conference on soft tissue sarcoma (STS). Identification of controversial topics in the interdisciplinary management of STS. Modified Delphi process and final voting by 62 European panellists. Proposals for scientific questions, which need addressing in the future. Addition to the existing STS guidelines.